Analisis Kondisi Sosial Ekonomi Terhadap Penerima Bantuan Kartu Keluarga Sejahtera (KKS) Di Sumatera Barat - Wulandari, Khoirunnisa; Yeniwati, Yeniwati (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2023)
The main objective of this research is to find out how socio-economic conditions affect recipients of the Prosperous Family Card Assistance (KKS) in West Sumatra. This study is using the 2017 Susenas Core data with a sample of 19 districts/cities in West Sumatra Province in 2017. We employ the logistic regression analysis (Logistic Regression) with 2,511 observations to infer the social economic condition of household in determining an household as the KKS recepient. The estimation results shows that there is one variable that has no influence on the Head of the Household who receives the Prosperous Family Card assistance, namely the variable of residence ownership with a probability value of 0.075. While the other three variables, namely education level, occupation, and health insurance, have a significan.